Integrated estimation of parameters of radio transmitter power amplifier with automatic mode adjustment by two-frequency test signal - P. V. Sak (Омский научный вестник)
Comparative estimation of energy parameters of power amplifiers of single-band radio transmitters using automatic mode adjustment using a deterministic two-frequency test signal instead of a random single-band signal modulated by speech is investigated in the work. Relationships are found that allow judging the power consumption of the terminal stage of the power amplifier with automatic mode adjustment under various types of modulation based on the results of measurements obtained during tests. The ratios between the power consumption of the output stage when amplifying the random speech signal and amplifying the deterministic two-frequency test signal are obtained both without taking into account losses in the controlled power supply and taking into account such losses. Method is proposed for calculation of energy gain and efficiency factor (efficiency) when applying automatic control of supply voltage of output cascades of shortwave transmitters intended for modulation with speech signals. The loss in the regulated power supply has been estimated. The advantage of power amplifier circuits with automatic mode adjustment is justified.